2021
DOI: 10.1200/jco.20.02341
|View full text |Cite
|
Sign up to set email alerts
|

Eprenetapopt (APR-246) and Azacitidine in TP53-Mutant Myelodysplastic Syndromes

Abstract: PURPOSE Approximately 20% of patients with TP53-mutant myelodysplastic syndromes (MDS) achieve complete remission (CR) with hypomethylating agents. Eprenetapopt (APR-246) is a novel, first-in-class, small molecule that restores wild-type p53 functions in TP53-mutant cells. METHODS This was a phase Ib/II study to determine the safety, recommended phase II dose, and efficacy of eprenetapopt administered in combination with azacitidine in patients with TP53-mutant MDS or acute myeloid leukemia (AML) with 20%-30% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
232
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(244 citation statements)
references
References 38 publications
10
232
0
2
Order By: Relevance
“…However, this observation is not supported by data from controlled clinical trials [4,33]. New agents, such as the p53 reactivator APR-246 or the monoclonal anti-CD47 antibody magrolimab that have shown The underlined figures indicate the most common mutation found by each study, whereas the bold figures denote the three most common mutations that each study reported F, female; M, male, NR, not reported promising activity in this high-risk subset of AML, are currently in clinical development [34,35]. Apart from the limited transplant access, the poor OS and RFS rates of our patients were possible because age > 65 years and unfavorable genetic mutations (especially the TP53 mutation) were adverse factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, this observation is not supported by data from controlled clinical trials [4,33]. New agents, such as the p53 reactivator APR-246 or the monoclonal anti-CD47 antibody magrolimab that have shown The underlined figures indicate the most common mutation found by each study, whereas the bold figures denote the three most common mutations that each study reported F, female; M, male, NR, not reported promising activity in this high-risk subset of AML, are currently in clinical development [34,35]. Apart from the limited transplant access, the poor OS and RFS rates of our patients were possible because age > 65 years and unfavorable genetic mutations (especially the TP53 mutation) were adverse factors.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have shown that eprenetapopt is efficient on its own, while it is also synergizing with AZA in TP53-mutated MDS and AML cell lines and in TP53-mutated cells from MDS and AML patients [ 75 ]. A phase Ib/II study to determine the safety and efficacy of eprenetapopt (APR-246) with AZA in patients with TP53 -mutant MDS or AML with a low percentage of blasts has recently been published, with highly promising results [ 55 ] ( Table 2 ). The ORR of the 51 patients enrolled (40 MDS) was 71%, with CR in 44%.…”
Section: High-risk Mds (Hr-mds)mentioning
confidence: 99%
“…Indeed, the immunologic effect by HSCT appears to be largely ineffective in this subgroup, possibly, also due to an immunosuppressive phenotype conferred by the TP53 mutant [37]. Alternative therapeutic approaches should be explored for this category of patients, including the incorporation of a novel agent capable of restoring the normal TP53 conformation and function, such as APR-246 [38], and the introduction of maintenance strategies after HSCT in order to enhance the graft versus leukemia effect.…”
Section: Summary Of Available Evidence About Intensive Approachesmentioning
confidence: 99%